Penerapan Metode Analytical Hierarchy Process dalam Pengambilan Keputusan Pengembangan Sistem Pelayanan Air Minum Kecamatan Patumbak di Kabupaten Deli Serdang - T. Rizki Muda Keulana (Syntax Idea)
Water is one of human basic need and social-economics rights which should provided by governmnet. Water supply have 5 importants indicators : quality, quantity, continuity, system reliability and tariff affordability. This requires decision making process in determining the development of drinking water supply. In this research, Analytical Hierarchy Process (AHP) and Point Allocation (PA) methods were developed in determining decision making related to drinking water supply in Patumbak District, Indonesia, which currently has as shortage service coverage (30,33%). The expected results of this research are able to provide input to stakeholders in making decisions in the development of water supply systems within 4 (four) main criteria. The Preferences used were opinions of all stakeholders who were interviewed and produced economic (0,446), environmental (0,242), technical (0,104) and socio-cultural (0,104) as its criteria weight. In the results of sensitivity analysis, rangking changes occur at the smallest weight changes in environmental criteria, with AHP Method’s result 7,50% and PA Method’s 3,75% as their sensitivity value.